Fuzzy Bases - Azizi, Amir; Sorooshian, Shahryar (IDOSI Publication, 2013)
This study tries to provide a comprehensive understanding of theories of fuzzy approach and their application methods. This paper can be a note for those who are interested to apply fuzzy theories in their researches. Text starts with theoretically review fuzzy theories and follows by an introduction to application methods of these theories.